Yield performance evaluation of kabuli and desi chickpea (Cicer arietinum L.) varieties under rainfed condition - Eshetu, Yohannes Seyoum; Woldemichael, Tesfu Mengistu; Gebreegziabher, Zelalem Fisseha (Journal of Scientific Agriculture, 2024)
Chickpea is one of Ethiopia’s main grain legume crops and it is third most important export legumes after faba bean and haricot bean. The performance information for chickpea cultivars under varying environmental conditions in the Somali region is limited. A field experiment was conducted to test the adaptability of 14 released chickpea varieties (both kabuli and desi types) at Kebribeya and Jigjiga in 2021. The experiment was carried out using a complete randomized block design with three replications for both types separately. The analysis of variance computed for seven traits for each location and over the location revealed the presence of significant variability between varieties. Variety by location interaction was highly significant for most yield and yield related for both types, this indicated that location-specific variety selection is needed. Hence, among the tested kabuli types, Koka and Hora for Kebribeya and Ejera and Koka for Jigjiga were selected based on their grain yield potential and other yield and yield-related traits. Regarding the desi-type Dalota and Dimtu for Kebribeya and Dalota, Natoil and Teketay for the Jigjiga location were the best high-yielder varieties among tested varieties. Additionally, the phenotypic correlation between traits revealed that most traits were associated with grain yield. Specifically, days to maturity and the number of pods per plant were highly correlated with grain yield in both types and were also used as important traits for variety selection. Therefore, the selected varieties from both chickpea types are recommended for popularization in study areas and other similar agroecology.